ABOUT JANE AUSTIN'S NOVEL EMMA - Nekboyeva Mahliyo Turaqulovna (Web of Journals Publishing, 2024)
This article talks about one of the great bees "Emma" by the famous writer Jane Austen, as well as about the human psyche in it.
Keywords: Poetry, emotion, Mary Wollstonecraft, Mansfield, Emma Woodhouse, Highbury, Frank Churchill, spirituality, love.